Comparison of Piezosurgery and Conventional Rotary Instruments for Removal of Impacted Mandibular Third Molars: A Randomized Controlled Clinical and Radiographic Trial - Hani Arakji; Mohamed Shokry; Nayer Aboelsaad (Hindawi Limited, 2016)
The purpose of this study was to test the effect of the surgical removal of impacted mandibular third molars using piezosurgery versus the conventional surgical technique on postoperative sequelae and bone healing. Material and Methods. This study was carried out as a randomized controlled clinical trial: split mouth design. Twenty patients with bilateral mandibular third molar mesioangular impaction class II position B indicated for surgical extraction were treated randomly using either the piezosurgery or the conventional bur technique on each site. Duration of the procedure, postoperative edema, trismus, pain, healing, and bone density and quantity were evaluated up to 6 months postoperatively. Results. Test and control sites were compared using paired t-test. There was statistical significance in reduction of pain and swelling in test sites, where the time of the procedure was statistically increased in test site. For bone quantity and quality, statistical difference was found where test site showed better results. Conclusion. Piezosurgery technique improves quality of patient's life in form of decrease of postoperative pain, trismus, and swelling. Furthermore, it enhances bone quality within the extraction socket and bone quantity along the distal aspect of the mandibular second molar.